Bacteraemia in Kenyan children with sickle-cell anaemia: a retrospective cohort and case-control study. - Williams, T; Uyoga, S; Macharia, A; Ndila, C; McAuley, C; Opi, D; Mwarumba, S; Makani, J; Komba, A; Ndiritu, M; Sharif, S; Marsh, K; et al. (2009)
BACKGROUND: In sub-Saharan Africa, more than 90% of children with sickle-cell anaemia die before the diagnosis can be made. The causes of death are poorly documented, but bacterial sepsis is probably important. We examined the risk of invasive bacterial diseases in children with sickle-cell anaemia. METHODS: This study was undertaken in a rural area on the coast of Kenya, with a case-control approach. We undertook blood cultures on all children younger than 14 years who were admitted from within a defined study area to Kilifi District Hospital between Aug 1, 1998, and March 31, 2008; those with bacteraemia were defined as cases. We used two sets of controls: children recruited by random sampling in the same area into several studies undertaken between Sept 1, 1998, and Nov 30, 2005; and those born consecutively within the area between May 1, 2006, and April 30, 2008. Cases and controls were tested for sickle-cell anaemia retrospectively. FINDINGS: We detected 2157 episodes of bacteraemia in 38 441 admissions (6%). 1749 of these children with bacteraemia (81%) were typed for sickle-cell anaemia, of whom 108 (6%) were positive as were 89 of 13 492 controls (1%). The organisms most commonly isolated from children with sickle-cell anaemia were Streptococcus pneumoniae (44/108 isolates; 41%), non-typhi Salmonella species (19/108; 18%), Haemophilus influenzae type b (13/108; 12%), Acinetobacter species (seven of 108; 7%), and Escherichia coli (seven of 108; 7%). The age-adjusted odds ratio for bacteraemia in children with sickle-cell anaemia was 26.3 (95% CI 14.5-47.6), with the strongest associations for S pneumoniae (33.0, 17.4-62.8), non-typhi Salmonella species (35.5, 16.4-76.8), and H influenzae type b (28.1, 12.0-65.9). INTERPRETATION: The organisms causing bacteraemia in African children with sickle-cell anaemia are the same as those in developed countries. Introduction of conjugate vaccines against S pneumoniae and H influenzae into the childhood immunisation schedules of African countries could substantially affect survival of children with sickle-cell anaemia. FUNDING: Wellcome Trust, UK.